2017
DOI: 10.1039/c7fd00082k
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of non-covalent interactions between cationic N-phenylviologens and halides by electrochemistry and NMR: the halogen bonding effect

Abstract: Five N-phenylviologen (PV) derivatives have been synthesized and their electrochemical behavior in the presence of halide anions has been studied. Further investigations were carried out byH and F NMR spectroscopy at different chloride concentrations. This is the first time a systematic study combines cyclic voltammetry and NMR spectroscopy in order to analyse the contribution of halogen bonding among the various non-covalent interactions between iodinated N-phenylviologens. The results show strong evidence fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…We attempted to verify the availability of the XBs in solutions and studied electrochemical behavior of 1−3 upon the addition of FIB in CH 2 Cl 2 solution by cyclic and differential pulse voltammetry techniques. 91,92 We used 1:20 molar ratios between any one of 1−3 and FIB to minimize competitive complex−solvent interactions, also those with the supporting electrolyte. In contrast to the previously studied adducts of FIB with the half-lantern Pt II 2 species displaying clear XB in solution, 31 no significant changes in oxidation potentials were observed conceivably because of the low concentration of the XB adducts in solution.…”
Section: Resultsmentioning
confidence: 99%
“…We attempted to verify the availability of the XBs in solutions and studied electrochemical behavior of 1−3 upon the addition of FIB in CH 2 Cl 2 solution by cyclic and differential pulse voltammetry techniques. 91,92 We used 1:20 molar ratios between any one of 1−3 and FIB to minimize competitive complex−solvent interactions, also those with the supporting electrolyte. In contrast to the previously studied adducts of FIB with the half-lantern Pt II 2 species displaying clear XB in solution, 31 no significant changes in oxidation potentials were observed conceivably because of the low concentration of the XB adducts in solution.…”
Section: Resultsmentioning
confidence: 99%
“…For 1a, two supplementary cathodic irreversible waves at -1. 19 and -1.39 V were recorded and can be attributed to the dissociative reduction of the C-I bonds.…”
Section: Electrochemically Driven Interfacial Halogen Bonding Betweenmentioning
confidence: 95%
“…The groups of Beer as well as Schöllhorn and Fave also investigated a range of other redox transducers in XB anion sensors, such as viologen-based systems for detection of various halides, whereby all studies revealed an important contribution of XB in obtaining (enhanced) voltammetric responses. [147][148][149] The latter groups further conducted a range of systematic studies into XB iodo-tetrathiafulvalene (TTF) voltammetric sensors. 138,150 As shown in Fig.…”
Section: Redox-active Sensorsmentioning
confidence: 99%